1973
DOI: 10.3171/jns.1973.38.6.0698
|View full text |Cite
|
Sign up to set email alerts
|

Experience with 88 consecutive cases of brain abscess

Abstract: The records of 88 patients with intraparenchymal brain abscess treated during 1946-1971 were reviewed. The incidence of brain abscess did not decline significantly during this period. The overall mortality rate was 36.4%, and the operative mortality rate 29.1%. The most frequent findings were alteration of consciousness, headache, and elevated peripheral white blood cell count; fever, hemiparesis, seizures, neck stiffness, nausea and vomiting, and papilledema were less common. Lumbar puncture was a definite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
2
9

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(63 citation statements)
references
References 20 publications
0
51
2
9
Order By: Relevance
“…In our series, it was 10.58 %, while Morgan et al (1973) [6], Gupta et al (1990) and Menon& Bhardwaj et al (2008) observed it in 13.63%, 16.25% and 8% respectively. We found two cases of brain abscess due to deficiency in cell mediated immunity i.e.…”
Section: Aetiological Factorsmentioning
confidence: 68%
“…In our series, it was 10.58 %, while Morgan et al (1973) [6], Gupta et al (1990) and Menon& Bhardwaj et al (2008) observed it in 13.63%, 16.25% and 8% respectively. We found two cases of brain abscess due to deficiency in cell mediated immunity i.e.…”
Section: Aetiological Factorsmentioning
confidence: 68%
“…Entre el 70 y el 97% de los pacientes tienen cefalea, que suele ser progresiva y refractaria al tratamiento habitual, y aparece bien aislada, bien asociada a síntomas de hipertensión intracraneal 1,5,6,11,17,28 . En nuestra serie se observa en las dos terceras partes de los pacientes.…”
Section: Discussionunclassified
“…La fiebre, que aparece aproximadamente en la mitad de los casos, suele ser de bajo grado, de modo que una temperatura muy elevada debe hacer sospechar una infección sistémica o meningitis concomitante 11 . Son también frecuentes en las distintas series las crisis epilépticas, que antes de la cirugía se dan entre un 25-50% 11,16,17,22 , aunque nosotros hemos recogido menor incidencia (17%). Otros síntomas menos frecuentes son el meningismo, la ataxia de la marcha, etc.…”
Section: Discussionunclassified
See 2 more Smart Citations